Vocal Harmony in Zaid Bin Ali Reading: الانسجام الصوتي في قراءة زيد بن علي (المجلة العربية للعلوم و نشر الأبحاث, 2021)
The Quran readings are considered to be a source of Arab linguistic heritage where they represent various linguistic phenomena characterized by many functional vocal ones. There is no doubt that Zaid Bin Ali contains several vocal phenomena that needs to be thought over deeply. Therefore, the importance of the study emerges where the vocal phenomena whose function was vocal harmony will be dealt by study and analysis to identify their types and influence on the structure of the word. It was followed by a number of results, the most important of which are: The dominant feature of the verbal performance of the reading of Zaid bin Ali is vocal harmony and lightness.